Mode-locked thulium doped fibre laser with copper thin film saturable absorber - Muhammad, Ahmad Razif; Ahmad, Muhammad Taufiq; Zakaria, Rozalina; Yupapin, Preecha Promphan; Harun, Sulaiman Wadi; Yasin, Moh (Taylor & Francis, 2019)
We demonstrate the generation of mode-locked Thulium-Doped Fibre Laser by employing a newly developed saturable absorber (SA) based on copper (Cu) thin film. The SA was prepared by depositing nano-sized particles of Cu onto the surface of polyvinyl alcohol (PVA) film through the E-Beam evaporation process. A stable mode-locking pulse train operating at 1951 nm was successfully generated by introducing the Cu PVA SA into a laser cavity. The laser generated a pulse train at the fundamental frequency of 8.5 MHz with a calculated minimum pulse width of 14.8 ps. This demonstration proves that the Cu PVA based SA is suitable for generating mode-locked fibre laser at 2 µm region. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.